Functional analysis of the IGF-system in milk. Issue 4 (August 2017) - Hoeflich, Andreas; Meyer, Zianka
Abstract : The development of milk during evolution is considered a more recent step to provide the neonate with adequate amounts of energy, nutrients, and specific hormonal signals thereby, granting a fast and efficient rate of postnatal growth and development. Since the insulin- or the insulin-like growth factor (IGF) systems were evolved much earlier, it can be assumed that the functionality of the IGF-system has been integrated into the novel matrix milk containing casein and whey proteins from the beginnings. In fact, IGFs and IGF-binding proteins (IGFBPs) are abundantly present in milk, which is particularly true for fore-milk or colostrum and the potential effects of milk-borne IGF-compounds on the consuming organisms have in fact been addressed by several studies. Those studies examined, if orally administered IGFs can be absorbed by the consumer's gastro-intestinal tract and thus contribute e.g. to the somatic growth of infants. A second line of studies assessed local effects of milk-borne IGFs on growth and development of the gastro-intestinal tract itself. Finally, distinct functions of isolated IGF-compounds for growth and involution of the mammary gland have also been provided in the past. While the consumption of milk seems not to represent a major source of endogenous IGFs, accumulating evidence indicates secondary effects of milk on the endogenous IGF-system, which may be mediated by micronutrients such as branched amino acids and metabolic programming. By contrast, direct effects on growth and development of oesophageal and intestinal cells have been observed if IGFs were administered orally.